STATISTICAL PROCESS CONTROL APPLIED TO MONITOR LOSSES IN THE MECHANIZED SUGARCANE HARVESTING - Paixao, Carla S. S.; Voltarelli, Murilo A.; Silva, Rouverson P. da [UNESP]; Borba, Mateus A. de P. [UNESP]; Torres, Luma S. [UNESP] (Soc Brasil Engenharia Agricola, 2020)
The mechanized sugarcane harvesting process is considered one of the major economic bottlenecks, with low operational efficiency and, mainly, high losses of stalks left in the field. In order to minimize these problems and assist in the improvement of processes, this study aimed to evaluate the losses in the mechanized sugarcane harvesting using statistical process control. The experimental design was completely randomized, based on the methodology of statistical process control with samples collected on five work fronts during the daytime and nighttime operation. The experiment was carried out in an agricultural area of a sugarcane mill in the municipality of Ribeirao Preto, SP, Brazil, on five sugarcane harvest fronts. Losses were measured using a 3.0 x 3.33-m frame, being divided into stump, loose piece + fixed piece, whole sugarcane, fragment, and total losses for each harvest front. The data were grouped into 50 weeks over the sugarcane-growing season, and statistical analyses were performed using the Minitab 16 (R) software. Losses of loose piece + fixed piece were higher than the losses of stump, whole sugarcane, and fragment. The total losses showed higher and lower losses for the fronts F5 and F4, respectively, compared to the others.
Keywords: harvester; visible losses; Saccharum spp.